Regioselective Double C–H Functionalization of Arenes via Aryl Thianthrenium Salt Analogues - Hamad, Aboubakr; Mrozowicz, Michał; Xie, Yuanhao; Ritter, Tobias (Synlett, 2023)
Directed C–H functionalization reactions are powerful tools for the rapid and selective syntheses of complex molecules. However, many existing C–H functionalization reactions require the presence of a preinstalled directing group that has to be either a part of the molecule or introduced onto an existing functional group. Here, we report analogues of thianthrene that can also function as directing groups for intermediate directed C–H functionalization and thereby permit regioselective 2,4- and 3,4-aromatic C–H difunctionalization of simple arenes in yields of 22–33% over three steps.
Keywords: sulfonium salts; C–H functionalization; directing group; linchpin; palladium catalysis